Yurii Mykolaiovych Pavlenko (22.04.1955 – 31.12.2015) - Institute for Nuclear Research (Ядерна фізика та енергетика)
Brief biography and scientific achievements of Yurii Mykolaiovych Pavlenko in connection with his death